Tüketici Yenilikçiliği, Algılanan Risk ve Ürün İlgileniminin Online Satın Alma Davranışı Üzerindeki Etkisi - Yapraklı, Şükrü; Gül, Başak (Muş Alparslan Üniversitesi, 2021)
While online shopping offers a huge market opportunity for manufacturers, it not only provides information but also offers consumers the opportunity to shop wherever and whenever they want. Online purchasing is any kind of shopping that can be made over the internet with various payment methods. It is possible to find many factors that influence online purchasing. Consumer innovativeness, perceived risk, and product involvement are among these factors. This study seeks to determine the impact of consumer innovativeness, perceived risk, and product involvement on online purchasing behavior. Study data were collected in September-October 2019. Face-to-face survey method was chosen as the data collection method and it was evaluated with 400 questionnaires within the scope of the research with the participation of individuals living in the province of Erzurum. For this study, the necessary permission was obtained with the decision of the Social and Human Sciences Scientific Research Publication Ethics Committee of Erzurum Atatürk University, dated 22.01.2020 and numbered 2020/01- 04. The obtained data were analyzed in the SPSS program and the frequency distributions of the participants were examined, reliability tests and regression analyses were performed. As a result of the research, it was found that consumer innovativeness, perceived risk, and product involvement have an impact on online purchasing behavior.

Online alışveriş üreticiler için büyük bir pazar fırsatı sunarken, tüketicilere de bilgi sağlamakla kalmayıp aynı zamanda istediği yer ve zamanda alışveriş yapma imkânı sunmaktadır. Online satın alma, çeşitli ödeme yöntemleri ile internet üzerinden yapılabilen her türlü alışveriştir. Online satın almaya etki eden birçok faktör vardır. Tüketici yenilikçiliği, algılanan risk ve ürün ilgilenimi de bu faktörlerdendir. Bu çalışmada, tüketici yenilikçiliği, algılanan risk ve ürün ilgileniminin online satın alma davranışı üzerindeki etkisi belirlenmeye çalışılmıştır. Çalışma verileri 2019 yılı Eylül-Ekim zaman aralığında toplanmıştır. Veri toplama metodu olarak yüz yüze anket yöntemi seçilmiş ve Erzurum ilinde yaşayan bireylerin katılımı ile araştırma kapsamında 400 anket ile değerlendirilme yapılmıştır. Bu çalışma için, Erzurum Atatürk Üniversitesi Sosyal ve Beşeri Bilimler Etik Kurulu’nun 22.01.2020 tarih ve 2020/01-04 nolu kararı ile çalışmanın etik kurallara uygun olduğuna dair gerekli izin alınmıştır. Elde edilen veriler SPSS programında analiz edilerek katılımcıların frekans dağılımları incelenmiş, faktör analizi ile test edilmiş, güvenilirlik testleri ve regresyon analizleri yapılmıştır. Araştırma sonucunda, tüketici yenilikçiliği, algılana risk ve ürün ilgilenimi faktörlerinin online satın alma davranışı üzerinde etkili olduğu görülmüştür.
The Effect of Consumer Innovation, Perceived Rısk and Product Involvement on Online Purchase Behavior
anemon
Keywords: Consumer İnnovation; Perceived Risk; Product İnterest; Online Purchase; Tüketici Yenilikçiliği; Algılanan Risk; Ürün İlgilenimi; Online Satın Alma